Examining the Effect of Gender and Educational Level on Iranian EFL Graduate Students’ Perceived Reasons for Committing Plagiarism (GIST – Education and Learning Research Journal, 2020)
As an unethical behavior, plagiarism refers to using other people’s words or ideas without appropriately acknowledging the source (Delvin & Gray, 2007). Numerous scholars from different parts of the world have attempted to get into the root of this problem by identifying the underlying factors which contribute to such academic misconduct. In a similar vein, the present study aimed at examining the role of gender and educational level of Iranian EFL graduate students in determining the main reasons for plagiarism commitment from their point of view. To this end, a convenient sample of 159 M.A. and Ph.D. students partook in the study. To gather the necessary data, a 32-item Likert-Type questionnaire was administered whose results were subjected to a two-way MANOVA. Results of the study indicated that neither the students’ gender or educational level nor the interaction effect of these two variables had any significant effect on the reasons for engaging in plagiarism. Descriptive statistics, however, showed that students’ personal and attitudinal characteristics took on paramount importance compared to other factors. This can signal the intentionality of plagiarism among Iranian EFL graduate students, thereby suggesting the need for making more informed decisions on how to deal with this problem.
Keywords: educational level; gender; Iranian EFL graduate students; plagiarism